Persepsi Mahasiswa tentang Pengelolaan Pesantren Kampus di IAIN Samarinda - Idris, Muhammad (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2016)
IAIN Samarinda recruits the students not only from the Islamic senior high schools but also from non Islamic or other public schools. IAIN Samarinda is responsible to create the intellect-religious Moslem leaders who are able to use his/her proven beneficial scholar. IAIN Samarinda also tries to create alumni who able to give a positive profesional contribution to the society. One of the distinctive programs of IAIN Samarinda is peskam. This program is held by teaching English and Arabic and other Islamic lesson programs. This program is also targeted to create a professional-religious alumnus which is using English and Arabic as the medium of communication. This is a descriptive qualitative research design. The population of this study is about 144 students. They are the students of IAIN Samarinda who are taking peskam and live at the dormitory. The sample of the study is 36 students. The researcher used questionnaires to get the data. Then, the data were analyzed using Miles and Hubberman’ interactive model; data collection, data reduction, data display, and data display. The result of findings shows that in terms of planning, the students claim that peskam is a good program. In the aspects of organizing, actuating, and controlling, the students argue that they have not been performed yet.